2023
DOI: 10.3390/jcm12062424
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, Diagnosis and Management of Squamous Cell Carcinoma and Pseudoepithelial Hyperplasia Secondary to Red Ink Tattoo: A Case Series and Review

Abstract: The increasing popularity of tattooing has paralleled an increase in associated cutaneous reactions. Red ink is notorious for eliciting cutaneous reactions. A common reaction is pseudoepitheliomatous hyperplasia (PEH), which is a benign condition closely simulating squamous cell carcinoma (SCC). Differentiating PEH from SCC is challenging for pathologists and clinicians alike. The exact pathogenesis of these lesions secondary to red ink is not known, and there are no sources outlining diagnostic and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…A study of multiple tattoo inks showed high levels of heavy metals and other carcinogenic compounds, including azo dyes, which are used to make pigmented tattoo inks [7]. The red pigment has the highest association with squamous neoplasms [1,7,9,11], with some studies reporting up to 75% of squamous neoplasms occurring in red tattoo ink [3]. Previously, red ink in the tattooing industry contained high levels of mercury sulfide, which was thought to contribute to carcinogenesis [5,7,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study of multiple tattoo inks showed high levels of heavy metals and other carcinogenic compounds, including azo dyes, which are used to make pigmented tattoo inks [7]. The red pigment has the highest association with squamous neoplasms [1,7,9,11], with some studies reporting up to 75% of squamous neoplasms occurring in red tattoo ink [3]. Previously, red ink in the tattooing industry contained high levels of mercury sulfide, which was thought to contribute to carcinogenesis [5,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The red pigment has the highest association with squamous neoplasms [1,7,9,11], with some studies reporting up to 75% of squamous neoplasms occurring in red tattoo ink [3]. Previously, red ink in the tattooing industry contained high levels of mercury sulfide, which was thought to contribute to carcinogenesis [5,7,9]. A shift has been made toward using organic dyes containing azo pigments, a known carcinogen, and instances of malignancy continue to be reported with the organic dyes [1,5,7,9,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations